Prerequisites and opportunities for the use of the 5S principles in the company laboratory in an organic mill - Dziuba, Szymon; Cierniak-Emerych, Anna (Przesłanki i możliwości zastosowania zasad 5S w laboratorium przyzakładowym ekomłyna, 2019)
The success of economic organizations depends on searching for new ways of maintaining and increasing competitive advantage. This is particularly true for the food industry and, in particular, the organic food processing sector, where consumers expect high-quality foods containing macronutrients and micronutrients that are essential for the proper functioning of the human body. With this in mind, managers relatively often use sophisticated tools and technologies to solve problems in these business entities rather than using existing and verified tools and technologies. This concerns especially the solutions which are based on the assumptions of common sense, such as the 5S method. In this context, it was considered appropriate to try to implement the 5S principles in the laboratory of a company producing organic flour. The case study method was employed to analyse the possibility of implementation of 5S in the laboratory. The empirical examinations were based on open observation, and free-form interviews with managers and laboratory workers. The available recorded materials were used. Using the analysis of the collected information, an attempt was made to show the prerequisites and opportunities for the implementation of 5S
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 179-190
Keywords: 5S; ecology; kaizen; food quality; milling; ekologia; jakość żywności; młynarstwo